An experience in building a parallel and distributed problem-solving environment - Cunha, J. C. (2020)
We describe our experimentation with the design and implementation of specific environments, consisting of heterogeneous computational, visualization, and control components. We illustrate the approach with the design of a problem-solving environment supporting the execution of genetic algorithms. We describe a prototype steering parallel execution, visualization, and steering. A life cycle for the development of applications based an genetic algorithms is proposed.